The importance of veterinary science in our college course - Yeoman, Charles Ernest (My University, 1892)
Introduction: In our College course of study we have laid down for us what is considered the very best for the purpose to be attained. Development and practical knowledge are the watch words and go hand in hand. The knowledge we obtain is of that broad general character that can be applied to the arts and sciences, relating especially to Agriculture. It is upon this basis that we have an institution like the Kansas State Agricultural College, fostered by the State and the United States. The course of study is so planned that the student receives a gradual development. One study preceded and paving the way for its successor –Each receiving its due proportion of time, which will depend largely upon the nature and importance of the subject.
The importance of veterinary science
Citation: Yeoman, Charles Ernest. The importance of veterinary science in our college course. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Veterinary science; Vet; College; Theses; Manuscripts (documents)